Economic sustainable development goals: Assessments and perspectives in Europe. (20th June 2022) - D'Adamo, Idiano; Gastaldi, Massimo; Morone, Piergiuseppe
Abstract: The Sustainable Development Goals (SDGs) are a shared blueprint to support countries in their pursuit of reconciling economic growth with sustainability. This study considers 35 indicators related to the economic SDGs (SDG 7, SDG 8, SDG 9, SDG 11 and SDG 12) considering available data from 27 European countries in order to identify an aggregate value of sustainability in accordance with the multicriteria analysis. The results obtained make it possible to draw up a ranking in which Sweden comes out on top, ahead of Denmark. Denmark, along with Austria, are the only two countries to perform better than the European average in all 5 SDGs analyzed. In general, northern and western countries outperform other considered countries. The obtained multicriteria aggregate sustainability indicator shows a good linear fit with Gross Domestic Product (GDP) per capita. However, Luxembourg and Ireland behave as outliers, showing a high GDP level misaligned from the multicriteria aggregate sustainability indicator. A distinguished characteristic of these countries is the very attractive taxation system, which, as it seems, has succeeded in prompting economic growth yet failing in reconciling it with sustainability objectives. These findings open up to reflections in which growth drivers should be aligned with sustainability targets.